Characterization of Secondary Metabolites from the Raphides of Calcium Oxalate Contained in Three Araceae Family Plants Using Laser Microdissection and Ultra-High Performance Liquid Chromatography-Quadrupole/Time of Flight-Mass Spectrometry. Issue 3 (June 2013) - Liang, Zhitao; Zhang, Jian; Wong, Lailai; Yi, Tao; Chen, Hubiao; Zhao, Zhongzhen
The dried stem tubers of Pinellia ternata (Thunb.) Breit, P. pedatisecta Schott and Typhonium flagelliforme (Lodd.) Blume from the Araceae family are used as Chinese medicines, namely Banxia, Zhangye Banxia and Shui Banxia, respectively. They have been reported to have a strong irritative effect on mucosa. Previous studies have indicated that the pure raphides of calcium oxalate contained in the stem tubers of three plants have attributed to this strong irritation. However, the processed products of the stem tubers of P. ternata, including Fabanxia, Qingbanxia and Jiangbanxia, have been found to have no irritative effects on mucosa. Currently, the secondary metabolites from the raphides of calcium oxalate contained in the stem tubers of P. ternata with its processed products, P. pedatisecta and T. flagelliforme were analyzed by means of laser microdissection and ultra-high performance liquid chromatography-quadrupole/time of flight-mass spectrometry. The results indicate that the stem tubers of P. ternata P. pedatisecta and T. flagelliforme mainly contain amino acids, fatty acids, cyclic dipeptides and alkaloids. The secondary metabolite profile of the stem tuber of P. ternata was different from those of its processed products, Fabanxia, Qingbanxia and Jiangbanxia. However, the secondary metabolites from their raphides of calcium oxalate all contained beta-sitosterol, sitosterol palmitate, trigonelline, octadecenoic acid, pedatisectine A and thymidine. The raphides of calcium oxalate from P. ternata, P. pedatisecta and T. flagelliforme do not include any specific irritants. The results indicated that the irritation induced by raphides of calcium oxalate of three Araceae family plants is not relevant to the secondary metabolites but relates to the special needle shape.